1994
DOI: 10.1007/bf02578247
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid turnover rates in the adipose tissues of the growing chicken (Gallus domesticus)

Abstract: The purpose of this study was to investigate the mobility of fatty acids in adipose tissue of the chicken and to determine whether adipose tissue dynamics are altered by dietary repartitioning agents. To this end, the turnover rates of fatty acids and triglycerides were estimated in adipose tissue of growing chicks by using isopentadecanoic acid (IPDA) and elaidic acid (EA) as marker dietary fatty acids. The half-life of IPDA in abdominal and sartorial adipose tissues of birds over 6 to 10 wk of age were 20 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…It is likely that the studied FAS had equilibrated; the plasma FAS of captive herring gulls Larus argentatus have been found to change with dietary switches in a few days (Käkelä et al 2005, and the half-life for fatty acids of avian adipose tissue is also relatively fast, about 20 d in chickens (Foglia et al 1994). The calibration factors calculated for the transfer of the signal from the diet to tissue differed considerably for individual fatty acids and in adipose tissue and plasma, and also somewhat in the 2 dietary groups (pelagic versus demersal).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the studied FAS had equilibrated; the plasma FAS of captive herring gulls Larus argentatus have been found to change with dietary switches in a few days (Käkelä et al 2005, and the half-life for fatty acids of avian adipose tissue is also relatively fast, about 20 d in chickens (Foglia et al 1994). The calibration factors calculated for the transfer of the signal from the diet to tissue differed considerably for individual fatty acids and in adipose tissue and plasma, and also somewhat in the 2 dietary groups (pelagic versus demersal).…”
Section: Discussionmentioning
confidence: 99%
“…Given the strong seasonal variation in body mass, with most breeding seabirds losing considerable body mass during the breeding season , Kalmbach et al 2004, it seems likely that the adipose tissue FAS of the birds returning to the breeding colony show signs of the winter diet (Foglia et al 1994, Herzberg & Skinner 1997, Katan et al 1997. However, it could be tested by sampling FAS in the adipose tissue of species of birds that are known to switch between completely different diets in summer and winter.…”
Section: Tissue Fasmentioning
confidence: 99%
“…Because the plasma FAS already show large changes 5 d after a switch of diet (Käkelä et al 2005), adipose tissue and muscle samples representing longer time windows were collected from fresh carcasses of dead great skuas. The turnover rates of fatty acid composition of adipose tissues vary according to metabolic status from a month to years, and are different for different fatty acids (Foglia et al 1994, Herzberg & Skinner 1997, Katan et al 1997. Thus, it is likely that at least slowly turning over components of adipose tissue FAS indicate winter diet of skuas, as these birds lose mass during the breeding season, but return to the colony in spring at heavy weights due to storage of reserves over winter (Furness 1987, Kalmbach et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Among different saturated fatty acids, stearic acid is not utilized well by the chick (Carver and Johnson, 1953); while polyunsaturated fatty acid is utilized wellby the birds (Crespo and Esteve-Garcia, 2001). Differences in fat deposition as the result of different dietary oil levels was reported by Foglia et al (1994)which might be due the association with metabolic differences between chicken lines (Foglia et al, 1994). An alternative therapeutic approach exploration was explained by Marion-Letellier et al, (2013) where it was reported that, thereis an impact of fatty acid on innate immunity.…”
Section: Introduction:-mentioning
confidence: 93%